2017
DOI: 10.2308/ajpt-51748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Change Process for Business Risk Auditing: Legitimacy Experiences of non-Big 4 Auditors

Abstract: SUMMARY The business risk auditing (BRA) approach was developed in the late 1990s and partly incorporated into audit standards in the early 2000s. As such, BRA was a significant innovation in audit methodology. In our interview study, we examine the experiences of 38 non-Big 4 auditors toward the theorization and diffusion of BRA. We use the widely recognized framework from Greenwood, Suddaby, and Hinings (2002), emphasizing the importance of legitimacy within an organizational field, to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Furthermore, the model stresses the importance of the theorisation stage to legitimise new ideas and practices. According to Van Buuren et al (2017), the theorisation stage had been largely ignored by academics. Its inclusion in the model of Greenwood et al (2002) resulted in a broad recognition in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the model stresses the importance of the theorisation stage to legitimise new ideas and practices. According to Van Buuren et al (2017), the theorisation stage had been largely ignored by academics. Its inclusion in the model of Greenwood et al (2002) resulted in a broad recognition in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Its inclusion in the model of Greenwood et al (2002) resulted in a broad recognition in the literature. Nevertheless, the qualitative research of these scholars also revealed several weaknesses of the model among which the iterative characteristics of the process (Blackler & Regan, 2006;Munir, 2005;Van Buuren et al, 2017). For example, Munir (2005) states that theorisation (stage 4) is an ongoing process, rather than being just one stage in the process (Munir, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De gevoelens van de legitimiteit van de verandering worden als essentieel verondersteld om een verandering tot een succes te maken. Uiteindelijk lijkt er bij de ontwikkeling en implementatie van de BRA-controleaanpak te weinig rekening gehouden te zijn met de legitimiteit van de vernieuwing (Van Buuren et al 2018):…”
Section: Leren Van Eerdere Innovaties: De Implementatie Van De Busine...unclassified
“…The BRA approach has continual interest from the research community (see, e.g., Fukukawa et al ., , ; Abdullatif and Al‐Khadash, ; Fukukawa and Mock ; van Buuren et al ., , ; Curtis et al ., ; Wright, ). It also continues to have detractors and sceptics about its added value, mainly to the small to mid‐sized segments of the audit industry (Humphrey et al ., ; Curtis et al ., ).…”
Section: Introductionmentioning
confidence: 99%